'Hidden from view'?: an analysis of the integration of women's history and women's voices into Australia's social history exhibitions. Issue 2 (1st February 2019) - Cramer, Lorinda; Witcomb, Andrea
ABSTRACT: 'Women have mostly been left out of history', boldly asserted Elizabeth Willis in her exhibition text for The Story of Victoria in 1985. Taking Willis' statement as a starting point, this article aims to trace firstly how women have been rewritten into Australia's social history exhibitions focusing on the use of voice as a strategy to do so, and secondly how these voices have changed historical master narratives – by allowing a shift from a big picture history to intimate and deeply personal stories that recast our understanding of the past in ways that are inclusive of gendered experiences. We investigate the use of the curatorial voice as reflected in Willis' work, aligning it with the notion of curatorial activism, before exploring the changing curatorial practices that expanded the potential for an interpretive approach that incorporated the voice of the subjects themselves as a central component in the telling of history. We then analyse the impact of these strategies on traditional understandings of the past through three exhibitions developed by Melbourne Museum over 30 years: The Story of Victoria, a successor exhibition The Melbourne Story, and their Great War centenary exhibition, WWI: Love & Sorrow .